Prior Informed Consent by Indigenous Communities for Access to Biological Resources and Related Traditional Knowledge: Procedures and Issues (Kanun: Jurnal Undang-undang Malaysia, 2022)
The Access to Biological Resources and Benefit Sharing Act 2017 (ABS 2017), which was enacted to implement the Convention on Biological Diversity and related protocols, requires prior informed consent by “indigenous communities” as a prerequisite for access to biological resources and traditional knowledge related to the resources available on the said community’s land. The indigenous communities referred to in the ABS 2017 are the orang asli communities in Peninsular Malaysia and natives in Sabah and Sarawak, just as defined by the relevant provisions in the Federal Constitution. The ABS 2017, which was gazetted on 18 December 2020, is important as it is the first law that allocated the requirement of informed consent of the indigenous community and the local community. This paper examines the provisions and procedures set by ABS 2017 to obtain prior informed consent and issues that could affect the objectives placed by the legislation. The research for this paper is mainly based on doctrinal legal research. This paper suggests that the lack of adequate recognition of the lands of the indigenous communities, especially the orang asli communities in Peninsular Malaysia, may hinder the objective that the law intends to achieve. This paper emphasizes that concerted efforts must be taken not only at the federal level but also the state level to protect the rights of indigenous communities as part of the initiative to achieve sustainable development.Keywords: Indigenous communities and law, access and benefit sharing law, prior informed consent.Full text: PDF